Perancangan Media Visualisasi Data Untuk Strategi Kegiatan Pemasaran Produk UMKM Pada E-Commerce Menggunakan Opencart Di Kecamatan Palupuah - Diva Suryani, Amelia; Annas, Firdaus; Hendra, Hendra (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Advances in information technology are currently developing very rapidly. The affordable combination of software and hardware is designed to meet a wide range of user needs. With the support of modern technology, it is now easier for users to obtain information and carry out transactions, equivalent to traditional methods. An example of the application of this technology is through the E-Commerce platform. E-commerce is an attractive option due to its significant advantages. In addition to making it easier for customers to see products directly, e-commerce also makes it possible to record all business activities efficiently, so as to become a solution that supports business sustainability in service activities for Micro, Small and Medium Enterprises (UMKM) in Palupuah Sub-district, Agam District. The goal is to increase the promotional power of household products and support global marketing communication so that customers can easily get the products they want. This research uses a Research and Development (R&D) model with a 4D development model, namely Define, Design, Develop and Decemination. The results of this research are in the form of a web-based promotional media with the help of Opencart application features, where the findings of this research show that Opencart is a supporting media that is able to increase the competitiveness of UMKM products in Palupuah sub-district, Agam district.